Motor responses to experimental Achilles tendon pain. Issue 5 (11th June 2010) - Henriksen, Marius; Aaboe, Jens; Graven-Nielsen, Thomas; Bliddal, Henning; Langberg, Henning
Abstract : Background: Achilles tendinopathies are characterised by pain and reduced function, and heavy-load exercises have been shown to be effective in the treatment of painful chronic Achilles tendinopathies. However, basic information is needed on how the biomechanics and neuromuscular control of the exercise are affected by Achilles tendon pain. Objective: The authors aimed to determine the effects of experimental Achilles tendon pain on motor function during one-legged weight bearing ankle plantar and dorsal flexion exercises. Methods: In a crossover study, with 16 healthy subjects tested on two different days separated by 1 week, three-dimensional ground reaction forces, ankle joint kinematics and surface electromyography (EMG) of the lower leg muscles were recorded during one-legged full weight-bearing ankle plantar (concentric) and dorsal (eccentric) flexion exercises. Measurements were done before, during and after either experimental Achilles tendon pain or a non-painful control condition. Pain was induced by intratendinous injections of hypertonic saline with isotonic saline injections as control. Joint kinematics, ground reaction force frequency contents and average EMG amplitudes were calculated. Results: Compared with the control condition experimental Achilles tendon pain reduced the EMG activity in agonistic, synergistic and antagonistic muscles, and increased the ground reaction force frequency content around 10 Hz, during both eccentric and concentric movement phases. Conclusions: These data show that experimental Achilles tendon pain causes widespread and reduced motor responses with functional effects on the ground reaction force.